1995
DOI: 10.1021/jm00001a019
|View full text |Cite
|
Sign up to set email alerts
|

Ac-[3- and 4-Alkylthioproline31]-CCK4 Analogs: Synthesis and Implications for the CCK-B Receptor-Bound Conformation

Abstract: It has been reported that substitution of the Met31 residue in Boc-CCK4 (Boc-Trp30-Met31-Asp32-Phe33-NH2, CCK33 numbering) by trans-3-propyl-L-proline yields a highly potent and selective CCK-B agonist. To further explore the structural requirements of the Met31 side chain in the receptor-bound conformation of CCK4, we have synthesized several Ac-CCK4 analogs containing substitution of Met31 by 3- and 4-(alkylthio)-substituted proline derivatives. To this end we have developed novel synthetic routes to enantio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 28 publications
4
51
0
Order By: Relevance
“…The synthesis of mercaptoproline derivatives has been described earlier [8] Binding studies for opioid receptors were identical to those described elsewhere [9,10]. They were performed at Washington University by Dr. Bruce Nock.…”
Section: Methodsmentioning
confidence: 99%
“…The synthesis of mercaptoproline derivatives has been described earlier [8] Binding studies for opioid receptors were identical to those described elsewhere [9,10]. They were performed at Washington University by Dr. Bruce Nock.…”
Section: Methodsmentioning
confidence: 99%
“…It was shown that conformational changes in practically all the peptide bonds of CCK-4 affect both affinity and selectivity of analogues for CCRs [26][27][28]. The PROSKURYAKOVA et al . structural modifications have been revealed that resulted in the analogues with pronounced selectivity toward CCR-1 [29].…”
Section: Resultsmentioning
confidence: 99%
“…However, we have previously found 24 that the absolute configuration of 3-MP residues in peptides can be assigned by selective reduction of the thiol to the corresponding Dor L-Pro containing analogue using Raney Ni. Comparison of 'H-nmr spectra and reverse phase high performance liquid chromatography ( RP-HPLC) retention times of the reduction products with known compounds allowed the stereochemical assignment to be made.…”
Section: Resultsmentioning
confidence: 99%
“…, which was prepared as previously described, 24 and BOG( NMe)Nle, which was graciously provided by Dr. Lakmal Boteju (The University of Arizona). Dimethylformamide (DMF) and CH2C12 were HPLC grade and stored over 4 A molecular sieves prior to use.…”
Section: Synthesismentioning
confidence: 99%